Teacher’s Acceptance of Students with Disability - Dimitrova Radojichikj, Daniela; Chichevska Jovanova, Natasha (Bulgarian Ministry of Education and Science, 2015)
The success of inclusive education depends on the acceptance and the ability of teachers to facilitate a good learning environment for all students. The purpose of this study was to investigate teachers’ acceptance of students with disability in their classroom, and the factors that influenced such acceptances. Quantitative research was used to gather information from general education teachers. The sample consisted of 122 teachers at 6 schools. The study found that the school teachers irrespective of their age and experiences have similar scores on Diversity Acceptance Checklist (DAC) of students with disabilities.
Keywords: acceptance, teachers, students with disability, inclusive education